2022
DOI: 10.1002/app.52196
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultraviolet‐protectivetextiles based on reduced graphene oxide‐silver nanocomposites on polyethylene terephthalate usingultrasonic‐assisted in‐situthermal synthesis

Abstract: The present research develops a novel in-situ synthesis method to produce a high performance nanocomposite coating on polyethylene terephthalate (PET) fabric as an enhanced UV-protective textile. Reduced graphene oxide-silver (rGO-Ag) multi-layer nanocomposite was in-situ synthesized on the PET fabric through the direct redox reaction between the Ag + ions and GO sheets by using ultrasonic and thermal treatment. The X-ray diffraction and field emission scanning electron microscope confirmed that the well-synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…One of the widely used nanoparticles in fabrics treatments is TiO 2 NPs due to its merits such as being antibacterial, self-cleaning and an excellent UV absorber [51,52]. This is due to the suitability of its band gap for absorption of rays in the range from 280-400 nm [12,15,[53][54][55]. Attia et al reported well dispersed TiO 2 NPs-and ZnO NPs-based textile fabrics coating individually and synergistically for various textile fabrics as shown in Figure 5 [12].…”
Section: Spherical Nanoparticles-based Coatingsmentioning
confidence: 99%
“…One of the widely used nanoparticles in fabrics treatments is TiO 2 NPs due to its merits such as being antibacterial, self-cleaning and an excellent UV absorber [51,52]. This is due to the suitability of its band gap for absorption of rays in the range from 280-400 nm [12,15,[53][54][55]. Attia et al reported well dispersed TiO 2 NPs-and ZnO NPs-based textile fabrics coating individually and synergistically for various textile fabrics as shown in Figure 5 [12].…”
Section: Spherical Nanoparticles-based Coatingsmentioning
confidence: 99%
“…This broad commercial use is due to the attractive physical and chemical properties of PET including high transparency, crystallization rate, high thermal stability, high mechanical properties, and high oxygen barrier. [1][2][3] It is estimated that the PET market will have a globally annual growth of 4.2% over the 5-year period from 2019 to 2024, increasing to 11 billion dollars in a period time of 2019-2024. 4 The two most used commercial processes for PET synthesis are presented in Figure 1; (i) esterification of terephthalic acid (TPA) with ethylene glycol (EG) followed by polycondensation and (ii) transesterification of dimethyl terephthalate (DMT) with EG followed by polycondensation.…”
Section: Introduction: Polyethylene Terephthalate and The Importance ...mentioning
confidence: 99%
“…Polyethylene terephthalate (PET) is a high‐volume polyester that is widely used in the packaging and textile industries. This broad commercial use is due to the attractive physical and chemical properties of PET including high transparency, crystallization rate, high thermal stability, high mechanical properties, and high oxygen barrier 1–3 . It is estimated that the PET market will have a globally annual growth of 4.2% over the 5‐year period from 2019 to 2024, increasing to 11 billion dollars in a period time of 2019–2024 4…”
Section: Introduction: Polyethylene Terephthalate and The Importance ...mentioning
confidence: 99%
“…16,17 Among all above materials; graphene-coated electroconductive textiles have been considered due to its ease of fabrication, high electrical conductivity, high surface area, great mechanical and wearing properties. 2,[18][19][20][21] It has been demonstrated that graphene oxide (GO), shows better coating properties on textiles due to the interaction between surface functional groups possibly via covalent, Van de Waals, and hydrogen bonding. 22,23 Reduction step is necessary to in situ convert of insulating GO into conductive reduced graphene oxide (rGO) through restoration of the honeycomb structure.…”
Section: Introductionmentioning
confidence: 99%
“…Using metals on textiles as conductive additives weaken the wearing properties including low permeability, low flexibility, increased weight and stiffness 16,17 . Among all above materials; graphene‐coated electroconductive textiles have been considered due to its ease of fabrication, high electrical conductivity, high surface area, great mechanical and wearing properties 2,18–21 . It has been demonstrated that graphene oxide (GO), shows better coating properties on textiles due to the interaction between surface functional groups possibly via covalent, Van de Waals, and hydrogen bonding 22,23 .…”
Section: Introductionmentioning
confidence: 99%